The Effect of Adding Fly Ash as a Filler on Lataston Mixtures (HRS-WC) - Purnomo, Farid Eko; Sholichin, Ibnu; Estikhamah, Fithri (Sustainable Civil Building Management and Engineering Journal, 2024)
Flexible pavement is the most commonly found type of road pavement in Indonesia. One asphalt mixture used in road construction is the Lataston Hot Rolled Sheet. The quality of road pavement can be enhanced by carefully selecting materials such as asphalt, aggregate, and filler. Filler plays a crucial role in asphalt pavement mixtures, and fly ash, containing pozzolanic elements, can be used as it fills voids and binds the mixture effectively. This research investigates the use of fly ash as a filler in the HRS-WC asphalt mixture, aiming to determine the optimum asphalt content, the best filler content, and the impact of fly ash as a filler on the performance of asphalt road materials in the Lataston Hot Rolled Sheet mixture (HRS-WC). The study employs the Marshall testing method in accordance with the 2018 General Bina Marga Specifications (Revision 2) The results of research on Marshall characteristics, obtained an optimum asphalt content value of 7.5% and an optimum filler content value of 1.35%. The addition of fly ash as a filler to the HRS-WC asphalt mixture increases the stability, durability and stiffness of the mixture by filling empty spaces, increasing density, reducing air voids and binding the asphalt mixture. However, excessive use of fly ash can make the mixture too stiff and reduce the flexibility of the pavement.